2019
DOI: 10.1111/apt.15296
|View full text |Cite
|
Sign up to set email alerts
|

The association between hepatocellular carcinoma and direct‐acting anti‐viral treatment in patients with decompensated cirrhosis

Abstract: Background: Direct-acting anti-viral therapy (DAA) has transformed hepatitis C virus (HCV) care, particularly in patients with decompensated cirrhosis. However, their impact on hepatocellular carcinoma (HCC) remains unclear. Aim: To use a national registry of patients with advanced liver disease to explore the relationship between DAA therapy and HCC. Methods: All patients with de novo HCC post DAA therapy were frequency matched with patients who did not develop HCC. Demographic, clinical and laboratory data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…There are several issues relevant to DAA therapy among patients with HCC. First, initial data suggested a potential increased risk of HCC recurrence, although subsequent studies did not support these findings . Second, in response to the controversy around HCC recurrence risk, the timing of DAA therapy in relation to HCC management became a point of debate .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several issues relevant to DAA therapy among patients with HCC. First, initial data suggested a potential increased risk of HCC recurrence, although subsequent studies did not support these findings . Second, in response to the controversy around HCC recurrence risk, the timing of DAA therapy in relation to HCC management became a point of debate .…”
Section: Introductionmentioning
confidence: 99%
“…First, initial data suggested a potential increased risk of HCC recurrence, [8][9][10][11][12][13][14] although subsequent studies did not support these findings. [15][16][17][18][19][20][21][22] Second, in response to the controversy around HCC recurrence risk, the timing of DAA therapy in relation to HCC management became a point of debate. [23][24][25] For example, some recommended DAA treatment deferral (ie at least 4-6 months) following potentially curative HCC management.…”
Section: Introductionmentioning
confidence: 99%
“…However, a current paper published in this journal found no difference between tumour size, progression or survival between viraemic and non-viraemic patients. 5 Few long-term follow-up data for more than 3 years after direct acting antiviral (DAA) treatment of HCV cirrhosis are available. We previously reported a cohort of 373 prospectively monitored patients with chronic hepatitis C receiving IFN-free therapies against HCV since January 2014.…”
Section: Editorsmentioning
confidence: 99%
“…We read with great interest the paper by Chang et al 1 Their study suggested that maternal tenofovir therapy decreased maternal hepatitis B virus (HBV) level and neonatal viremia and that positive neonatal HBV DNA was highly correlated with chronic HBV infection in children. However, we still have some concerns about the study.…”
Section: Editorsmentioning
confidence: 99%
“…response (SVR) rate than patients without HCC (68% vs 87%, P < .001, odds ratio: 3.13, 95%CI: 1.64-5.99). 1 We have several comments on the latter.…”
mentioning
confidence: 99%